2023
DOI: 10.3390/ijms24010735
|View full text |Cite
|
Sign up to set email alerts
|

Disulfiram Ophthalmic Solution Inhibited Macrophage Infiltration by Suppressing Macrophage Pseudopodia Formation in a Rat Corneal Alkali Burn Model

Abstract: FROUNT is an intracellular protein that promotes pseudopodia formation by binding to the chemokine receptors CCR2 and CCR5 on macrophages. Recently, disulfiram (DSF), a drug treatment for alcoholism, was found to have FROUNT inhibitory activity. In this study, we investigated the effect of DSF eye drops in a rat corneal alkali burn model. After alkali burn, 0.5% DSF eye drops (DSF group) and vehicle eye drops (Vehicle group) were administered twice daily. Immunohistochemical observations and real-time reverse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Although there are reports of macroscopic observation with gelatin embedding [ 10 ], it was necessary to use a separate specimen for each of those microscopic morphological changes and cellular observations. In addition, IHC with LV-SEM has been used in the renal region [ 11 , 12 , 13 ], but there are few reports of its use for observation of the eye [ 14 , 15 ]. In this study, we succeeded in preparing paraffin-substitutable specimens from gelatin-embedded specimens by using low-melting-point gelatin.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are reports of macroscopic observation with gelatin embedding [ 10 ], it was necessary to use a separate specimen for each of those microscopic morphological changes and cellular observations. In addition, IHC with LV-SEM has been used in the renal region [ 11 , 12 , 13 ], but there are few reports of its use for observation of the eye [ 14 , 15 ]. In this study, we succeeded in preparing paraffin-substitutable specimens from gelatin-embedded specimens by using low-melting-point gelatin.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism by which disulfiram triggers these aversive physical reactions is, at least in part, somewhat understood. However, new studies suggest novel pharmacodynamic roles for disulfiram; including the treatment of opioid use disorder and therapy resistance [20], preventing sepsis and tumor growth [5], and in regulating macrophage-elicited immune response [21].…”
Section: Pharmacodynamics Of Disulfiram On the Metabolism Of Cocaine ...mentioning
confidence: 99%
“…Disulfiram (DSF), a drug treatment for alcoholism, has been found to have FROUNT (a macrophage stimulator) inhibitory activity. Ikebukuro et al showed that DSF eye drops reduced macrophage accumulation in a rat corneal alkali burn model [17].…”
mentioning
confidence: 99%